Changing donor trends in assistance to agricultural research and development in Africa South of the Sahara - Pingali, Prabhu L.; Spielman, David J.; Zaidi, Fatima (International Food Policy Research Institute, 2016)
This chapter examines one facet of this resourcing challenge—the role and contribution of the donor community and official development assistance (ODA) to AR4D. Specifically, it examines historical and emerging trends in the international donor community in terms of who is investing, how much they are investing, and where their investments are targeted. The chapter goes on to explore the potential impacts of these donor trends on future human and agroecological landscapes, with a particular focus on SSA.